Formulation of a Robust National Rural Sector Program in Burkina Faso: What new themes have emerged from the socio-economic and climate scenarios process? - Zougmoré, Robert B.; Rutting, Lucas; Sidibé, Amadou; Ouédraogo, Joachim; Zida, Mathurin; Rabdo, Abdoulaye; Ouédraogo, Mathieu; Balinga, Michael; Vervoort, Joost M.; Partey, Samuel T.; Palé, Rémy; Ouédraogo, Moumini; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Under the partnership initiated in 2015 between the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the Permanent Secretariat for Coordination of Agricultural Sector Policies (SP-CPSA), in collaboration with other CGIAR research programs and centers, an analysis of the National Rural Sector Program (PNSR) based on the CCAFS socio-economic and climate scenarios was conducted with the effective participation of rural sector stakeholders in Burkina Faso. Twenty-two (22) recommendations were made to allow for the effective mainstreaming of plausible socio-economic, environmental and climatic factors in the near and distant future, that will make PNSR II more robust to face future uncertainties related to climate change, global dynamics, socio-economic changes, changes in norms and values, etc. In addition, an exercise with all the stakeholders helped in translating the said recommendations into new actions and themes to be taken into account when formulating PNSR II. Discussions between the stakeholders also underscored the need for crosscutting involvement of research in the implementation of the activities of PNSR II.